The Identity Issues at the Perspectives of Chinese Geopolitical Strategies - Svyrydenko, Denys; Fatkhutdinov, Vasyl (Studia Warmińskie, 2019)
The article presents theoretical and methodological constructions of the analytics of the phenomenon of identity, modernized socio-cultural determinants of the content of European identity, updated the logic of transformation from the national-ethnic, historical and cultural principles of the interpretation of identity to modern politically motivated conceptualizations. The specificity of the discursive procedures of European identity in contemporary philosophical inventions is explored. The globalization context (one’s Asian-European dimension) was discovered on the problem of identity clash at the perspectives of Chinese geopolitical strategies (One Belt, One Road Initiative). The results of World Values Survey were interpreted for substantiation of conclusions.